Web cache replacement policies a pragmatic approach. - Kin-Yeung Wong (IEEE Network : the magazine of global information exchange)
Research involving Web cache replacement policy has been active for at least a decade. In this-article we would like to claim that there is a sufficient number of good policies, and further proposals would only produce minute improvements. We argue that the focus should be fitness for purpose rather than proposing any new policies. Up to now, almost all policies were purported to perform better than others, creating confusion as to which policy should be used. Actually, a policy only performs well in certain environments. Therefore, the goal of this article is to identify the appropriate policies for proxies with different characteristics, such as proxies with a small cache, limited bandwidth, and limited processing power, as well as suggest policies for different types of proxies, such as ISP-level and root-level proxies